Coastal Vulnerability Assessment for Future Sea Level Rise and a Comparative Study of Two Pocket Beaches in Seasonal Scale, Ios Island, Cyclades, Greece - Apostolia Komi; Alexandros Petropoulos; Niki Evelpidou; Serafeim Poulos; Vasilios Kapsimalis (Journal of Marine Science and Engineering, 2022)
The coastal zone may be considered as the location where the marine and land environments interact dynamically and coexist with human societies. Globally, natural and human systems are being severely threatened by the sea level rise related to climate change. The outcome between the dynamic relationship of coastal environments and marine processes, and the future sea level rise as predicted by scientific reports, is the vulnerability of coastal areas such as sandy beaches, pocket beaches and low-lying coastal areas. The current research aims to assess the coastal vulnerability of Ios Island, Cyclades, Greece for the next 100 years and to identify areas that are comparatively more vulnerable to future sea level changes. Moreover, the seasonal changes concerning sedimentological and morphological characteristics of two pocket beaches of Ios Island, Mylopotas and Magganari, are also examined. From the application of the Coastal Vulnerability Index, 92.37% of the total length of the coastline of Ios Island is characterized by a very low vulnerability as it consists of rocky shores and cliffs, while sandy and pocket beaches are characterized by a very high vulnerability. From the fieldworks and data processing, the seasonal changes mainly concern the seabed’s topography, the sediments’ texture of the collected sand samples, the foreshore and backshore topography, as well as seasonal shoreline displacement, using the Digital Shoreline Analysis System tool (DSAS).